The I Academic expedition to study the Kazakh steppe (Journal of history, 2019)
The article describes the history of the I-th academic expedition to study the Kazakh steppe. Along with this review of historiographical works which have been produced as a result of the expedition. It shows the target and approaches the study of the Kazakh steppe. The organization of the first academic expedition royal power in the territory of the Kazakh zhuzes. It opens up the path, the time of the expedition. Also sets out the diaries and travel notes. It reveals the mission of Charles Miller Kazakh-Jungar-Russian relationship. A review of the work of G.F Miller’s «History of Siberia», is determined by its value. It describes the content of the «Portfolios Miller.» The role I.K.Kirilov in learning Kazakh region and sets the value of the cards that he drew, works for the Russian Empire. We give information about managing I.K.Kirilov «Orynburgskoy» expedition and gathering materials needed for the colonial policy of tsarism. It affected his work on the preparation of «flourishing condition of All-Russian state.»